2021
DOI: 10.48550/arxiv.2101.01777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The subtlety of Ly-a photons: changing the expected range of the 21-cm signal

Itamar Reis,
Anastasia Fialkov,
Rennan Barkana

Abstract: We present the evolution of the 21-cm signal from cosmic dawn and the epoch of reionization (EoR) in an upgraded model including three subtle effects of Ly-α radiation: Ly-α heating, CMB heating (mediated by Ly-α photons), and multiple scattering of Ly-α photons. Taking these effects into account we explore a wide range of astrophysical models and quantify the impact of these processes on the global 21-cm signal and its power spectrum at observable scales and redshifts. We find that, in agreement with the lite… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 53 publications
(121 reference statements)
0
18
0
Order By: Relevance
“…maximum predicted depth, ≈ 250 mK of the global signal from simulations like those in Cohen et al (2017). However, more recent simulations, including Lyman-𝛼 and CMB heating, by Reis et al (2021) report a maximum predicted depth of ≈ 165 mK approximately 3 times shallower than the reported ≈ 500 mK signal from EDGES (Bowman et al 2018).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…maximum predicted depth, ≈ 250 mK of the global signal from simulations like those in Cohen et al (2017). However, more recent simulations, including Lyman-𝛼 and CMB heating, by Reis et al (2021) report a maximum predicted depth of ≈ 165 mK approximately 3 times shallower than the reported ≈ 500 mK signal from EDGES (Bowman et al 2018).…”
Section: Introductionmentioning
confidence: 83%
“…Visbal et al the Global Epoch of Reionization Signature, Bowman et al 2018) In 2018 the EDGES collaboration reported the detection of an absorption trough at 78 MHz (Bowman et al 2018). However, the reported feature is approximately 3 times deeper 2 than the current standard theoretical predictions (Reis et al 2021). While the excess depth can be explained theoretically with an excess radio background above the CMB (Bowman et al 2018;Feng & Holder 2018;Ewall-Wice et al 2018;Jana et al 2019;Mirocha & Furlanetto 2019;Reis et al 2020b) or interactions between dark matter and baryons (Barkana 2018;Fialkov et al 2018;Barkana et al 2018;Berlin et al 2018;Kovetz et al 2018;Muñoz & Loeb 2018;Slatyer & Wu 2018;Liu et al 2019) there are concerns about the data analysis and potential presence of systematics in the publicly available EDGES data (Hills et al 2018;Bradley et al 2019;Singh & Subrahmanyan 2019;Sims & Pober 2020;Bevins et al 2021a).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations